2014
DOI: 10.1007/s10554-014-0380-5
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide influences atherogenesis in aortas of ApoE−/−/LDLR−/− double knockout mice: a nano-CT study

Abstract: Plaque progression in atherosclerosis is closely connected to angiogenesis due to vasa vasorum (VV) growth. Objective of this study was to determine the unknown long-term effect of thalidomide on adventitial VV neovascularization and plaque progression using nano-focussed computed tomography (nano-CT). Proliferation and migration assays in human coronary artery endothelial cells (HCAEC) measured number of viable cells after incubation with thalidomide. Male ApoE−/−/LDLR−/− (AL) mice (n = 5) received a thalidom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…In further findings, Gõssl et al demonstrated that VV are not connected by a plexus but rather are end arteries ( 25 ). Using ex vivo micro-CT scans, we could demonstrate that this pathological sprouting pattern can also be observed in VV of small animal models of atherosclerosis, namely, apolipoprotein E −/− (ApoE)/LDLR −/− mice, and can be prevented by an antiangiogenic therapeutic approach ( 26 , 27 ). Moreover, structural hierarchy in adventitial VV was also later demonstrated in vivo in diseased LDLR −/− ApoB 100/100 mice by using high-resolution confocal microscopy ( 28 ).…”
Section: Correlation Between Arterial Wall Neovascularization and Athmentioning
confidence: 99%
See 1 more Smart Citation
“…In further findings, Gõssl et al demonstrated that VV are not connected by a plexus but rather are end arteries ( 25 ). Using ex vivo micro-CT scans, we could demonstrate that this pathological sprouting pattern can also be observed in VV of small animal models of atherosclerosis, namely, apolipoprotein E −/− (ApoE)/LDLR −/− mice, and can be prevented by an antiangiogenic therapeutic approach ( 26 , 27 ). Moreover, structural hierarchy in adventitial VV was also later demonstrated in vivo in diseased LDLR −/− ApoB 100/100 mice by using high-resolution confocal microscopy ( 28 ).…”
Section: Correlation Between Arterial Wall Neovascularization and Athmentioning
confidence: 99%
“…Moreover, these mice exert an extensive angiogenic activity in the adventitia and develop prominent adventitial and intimal plaque VV ( 19 , 100 ). Since these mice most closely mimicked atherosclerotic plaques in humans, we and others have used this model extensively during the last years to study VV formation in mice ( 26 , 27 , 101 ). It is commonly supported by cardiovascular pathologists trained in human and experimental pathology ( 102 , 103 ) that murine plaques most closely resemble human plaque morphology.…”
Section: Animal Models To Study Vv and Plaque Rupture In Atheroscleromentioning
confidence: 99%
“…Treatment with thalidomide preserved VV spatial density by 45% in high-cholesterol, diet-fed atherosclerosic pigs and was only 1.3-fold higher than that of normal pigs when compared with the 2.4-fold increase in the untreated group [ 171 ]. Reduced adventitial VV neovascularization and plaque progression after thalidomide treatment were also seen in Apoe −/− /Ldlr −/− double knockout mice [ 172 ]. The anti-angiogenic effect of thalidomide in atherosclerosis was accompanied by the inhibition of VEGF expression.…”
Section: Anti- and Pro-angiogenic Therapies On Vasa Vasorummentioning
confidence: 99%
“…An experimental animal study examined the long-term effect of thalidomide on adventitial VV neovascularization and plaque progression using nano-focused computed tomography (nano-CT) of descending aortas. [65] Proliferation and migration assays in human coronary artery endothelial cells (HCAEC) measured the number of viable cells after incubation with thalidomide in ApoE (-/-)/LDLR (-/-) (AL) mice (n = 5) and a control group. Thalidomide inhibited proliferation and migration of HCAEC dose-dependently and VV neovascularization decreased in number per cross section.…”
Section: Computed Tomography Componentmentioning
confidence: 99%